2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591354
|View full text |Cite
|
Sign up to set email alerts
|

CSDC — A nationwide screening platform for stroke control and prevention in China

Abstract: As a leading cause of severe disability and death, stroke places an enormous burden on Chinese society. A nationwide stroke screening platform called CSDC (China Stoke Data Center) has been built to support the national stroke prevention program and stroke clinical research since 2011. This platform is composed of a data integration system and a big data analysis system. The data integration system is used to collect information on risk factors, diagnosis history, treatment, and sociodemographic characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…An example of an IDR providing multiple services is the STRIDE architecture stack [ 18 ], which includes several services for data analysis or research data management. The articles describing METEOR [ 35 ], CSDC [ 34 ], models and simulation techniques for discovering diabetes-related factors (MOSAIC) [ 33 ], and Veterans Administration’s EHRs [ 32 ] provide further details about the integration of CDSS tools in the architecture. In these cases, the architecture model is divided into CDSS and data analysis modules, both of which communicate with the common database.…”
Section: Resultsmentioning
confidence: 99%
“…An example of an IDR providing multiple services is the STRIDE architecture stack [ 18 ], which includes several services for data analysis or research data management. The articles describing METEOR [ 35 ], CSDC [ 34 ], models and simulation techniques for discovering diabetes-related factors (MOSAIC) [ 33 ], and Veterans Administration’s EHRs [ 32 ] provide further details about the integration of CDSS tools in the architecture. In these cases, the architecture model is divided into CDSS and data analysis modules, both of which communicate with the common database.…”
Section: Resultsmentioning
confidence: 99%
“…In these contexts, inconsistent power supplies led to difficulties in EHR system implementation and intermittent internet availability constrained the development of web-based services [21–23]. However, a number of studies were able to leverage mobile networks and web-based platforms to wider benefit [24, 3538]. Studies reported different levels of maturity vis-à-vis EMR systems reach within a given context [27, 29, 3946].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically with regard to the workforce, many studies assessed end-user (or potential users) evaluation of previously implemented or planned ICT interventions [23, 31, 38, 42, 43, 45, 46, 48, 50]. Multiple studies highlighted interventions based around software, web-based platforms, or mobile technologies [21, 24, 25, 36, 37, 46]. Specific ICT interventions incorporated elements of automation [28, 30, 44, 49, 52]; data standardization or quality control [17, 22, 24, 3133, 35, 47]; data visualisations or data mapping [21, 35, 37, 38, 44, 45, 49]; and data analysis tools [22, 24, 29, 3941, 46].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations